2017
DOI: 10.1038/nature23681
|View full text |Cite
|
Sign up to set email alerts
|

Detecting recovery of the stratospheric ozone layer

Abstract: As a result of the 1987 Montreal Protocol and its amendments, the atmospheric loading of anthropogenic ozone-depleting substances is decreasing. Accordingly, the stratospheric ozone layer is expected to recover. However, short data records and atmospheric variability confound the search for early signs of recovery, and climate change is masking ozone recovery from ozone-depleting substances in some regions and will increasingly affect the extent of recovery. Here we discuss the nature and timescales of ozone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
184
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 209 publications
(193 citation statements)
references
References 102 publications
9
184
0
Order By: Relevance
“…Globally, the post-ODS peak trends vary generally between near-zero trends (NH extratropics) and positive trends of +0.7 % decade −1 (SH extratropics) with a statistical trend uncertainty of about 0.7 % decade −1 (2σ ) after 20 years of observations. We may therefore conclude that we are about to emerge into the phase of ozone recovery as is also shown by chemistry-climate and chemistry-transport models (e.g., Eyring et al, 2010;Shepherd et al, 2014;Solomon et al, 2016;Chipperfield et al, 2017). Both the regression applied to datasets (e.g., in our study) and models capture the dynamical variability well and their results are consistent.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Globally, the post-ODS peak trends vary generally between near-zero trends (NH extratropics) and positive trends of +0.7 % decade −1 (SH extratropics) with a statistical trend uncertainty of about 0.7 % decade −1 (2σ ) after 20 years of observations. We may therefore conclude that we are about to emerge into the phase of ozone recovery as is also shown by chemistry-climate and chemistry-transport models (e.g., Eyring et al, 2010;Shepherd et al, 2014;Solomon et al, 2016;Chipperfield et al, 2017). Both the regression applied to datasets (e.g., in our study) and models capture the dynamical variability well and their results are consistent.…”
Section: Discussionsupporting
confidence: 68%
“…The Antarctic September trend is barely significant at the 2σ level and confirms the findings of Solomon et al (2016). Changes in the regression model, use of different proxies, and considerations of inherent drift uncertainties can easily remove the significance (de Laat et al, 2015;Chipperfield et al, 2017). In contrast, the October trends are much smaller (about 3 % decade −1 ) and statistically insignificant, which is also in agreement with Solomon et al (2016).…”
Section: Trends In Polar Springsupporting
confidence: 77%
“…Newchurch et al 2003;Angell and Free 2009;Eyring et al 2010;Krzyścin 2010;Zhang et al 2014;Chipperfield et al 2017). However, some studies have shown that stratospheric ozone concentrations over different regions along the same latitude exhibit different recovery rates.…”
Section: Introductionmentioning
confidence: 99%
“…2) is employed. Although the ozone decline due to chemical processes has ceased and is likely beginning to reverse (Chipperfield et al 2017), here we just analyze the contribution of chemical processes to the ZAO trend over the period 1979-2015 and do not attempt to separate the 'ozone recovery' period from the 'ozone depletion' period. Figure 11a shows the linear trends of zonal anomalies of chemical TCO (see Sect.…”
Section: The Impact Of the Surface Temperature On Zao Trendmentioning
confidence: 99%
“…We then subtract the contribution of the step basis function from the model data, obtaining the corrected CTM data where the discontinuities have been removed. For more details about the SLIMCAT model see Chipperfield (2006) and Chipperfield et al (2015Chipperfield et al ( , 2017. Using CTM output as an evaluation and adjustment tool for coarsely distributed global ozone measurements is not a novel idea.…”
Section: Chemistry-transport Model (Ctm) Datamentioning
confidence: 99%